PENGELOMPOKAN PLASMA NUTFAH RAMBUTAN BERDASARKAN KARAKTER MORFOLOGI - Kuswandi, nFn; Nofiarli, nFn; Sparta, Andre; Andini, Mega; Hadiati, Sri; Marta, Nini; Yanda, Resta Patma (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2016)
Rambutan is a fruit native to Indonesia, which has a high diversity. Indonesian Tropical Fruit Research Institute has a rambutan germplasm collection. The objectives of the research were to identify and classify rambutan germplasm accessions based on morphological characteristics, in order to identify the specific characteristics important for the development of future varieties of rambutan. Collecting data on the 32 accession was conducted in Aripan Experimental Field, Indonesian Tropical Fruit Research Institute from September 2014 to February 2015. Characterization of morphology characters referred to as the Descriptor for Rambutan was published by IPGRI. Cluster analysis based on morphological characteristics successfully separated the accession of rambutan R7 and R11 with 30 other rambutan accessions with the dissimilarity coefficient of 45%. Accession R4 was similar to Sitangkue, R14 was similar to Korong Gadang, and R15 was similar to Sinyonya. Characteristics that can be used to distinguish each of the accession of rambutan were the width of seed, seed thickness, total soluble solids (TSS), fruit diameter, spintern texture and the spintern color. Accession R15 can be developed as a commercial variety, because it has a high yield, and shelf life associated with high fruit weight characteristics and thick rind.